2006
DOI: 10.1007/s00251-006-0093-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific associations between MICA-STR and nasopharyngeal carcinoma in a southern Chinese Han population

Abstract: Previous studies have identified several HLA-B specificities that are associated with nasopharyngeal carcinoma (NPC) in populations of Chinese descent, in particular HLA-B35, -B38, -B46, and -B58. Perhaps except for HLA-B46, other associations cannot be simply accounted for by the linkage disequilibrium between HLA-A and B loci. The human major histocompatibility complex (MHC) class I chain-related gene A (MICA) maps 46 kb centromeric to HLA-B and is highly polymorphic; it encodes a stress-inducible protein wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 47 publications
1
47
1
Order By: Relevance
“…We did not have serum samples from our cases and controls to examine associations with serum levels in childhood ALL. It is still unclear why there may be a sex effect in HLA complex associations, but in light of similar findings in other diseases (Meyer et al 2001;Fisher et al 2002;Hensiek et al 2002;Tian et al 2006), this aspect of the association we are reporting here warrants further study. In two rat models, HSP70 has a higher expression level in males in response to a viral infection (Klein et al 2004) or following acute tail-shock stress (Nickerson et al 2006) in lymphoid organs.…”
Section: Discussionsupporting
confidence: 50%
“…We did not have serum samples from our cases and controls to examine associations with serum levels in childhood ALL. It is still unclear why there may be a sex effect in HLA complex associations, but in light of similar findings in other diseases (Meyer et al 2001;Fisher et al 2002;Hensiek et al 2002;Tian et al 2006), this aspect of the association we are reporting here warrants further study. In two rat models, HSP70 has a higher expression level in males in response to a viral infection (Klein et al 2004) or following acute tail-shock stress (Nickerson et al 2006) in lymphoid organs.…”
Section: Discussionsupporting
confidence: 50%
“…The A10 STR allele (Table 2), which is associated exclusively with allele MICA*020, has thus far been found in just a single chromosome in a Hunan Han population of Southern China. 18 The STR_MICA alleles A5 and A9 occurred at high frequencies (420%) in all five Amerindian populations ( Table 2). In addition, A10 and the deletion of the MICA gene were frequent (47%) only in Kaingang, whereas A6 was frequent (9%) only in Guarani KaiowĂĄ.…”
Section: Resultsmentioning
confidence: 96%
“…The STR allele A10 has been found in a Hunan Han population of Southern China in a single chromosome, along with HLA-B*5801. 18 In the Kaingang population, the allele was found in a different haplotype, MICA*020-HLA-B*3505-HLA-Cw*0401. The Kaingang HLA-B35 alleles were -B*3501, -B*3506 or -B*3505, the latter two being exclusively found in Amerindians from South America and thought to have originated in this continent by gene conversion with HLA-B*3501 as the founding allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent finding has shown that polymorphisms or haplotype in the MMP2 promoter could possibly play a role in mediating susceptibility to NPC in Chinese populations (Zhou et al, 2007). As for the observation that NPC is more common in males than females, a gender association between exon5 of the MICA gene which increases susceptibility to NPC has been observed (Tian et al, 2006).…”
Section: Genetic Susceptibilitymentioning
confidence: 99%